PERBANDINGAN EFEKTIVITAS LAB INQUIRY DAN GUIDED INQUIRY LEARNING MODEL UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR TINGKAT TINGKAT SISWA KELAS XI IPA PADA BAB MEKANIKA FLUIDA - Jumilah Jumilah; Budi Jatmiko; Eko Hariyono (JPPS (Jurnal Penelitian Pendidikan Sains), 2021)
The research aims to describe the improvement of students’ Higher Order Thinking Skills (HOTs) and compare the differences in effectiveness between the two levels of the inquiry learning model. Two types of learning model levels were applied in this research, namely the Inquiry Lab and Guided Inquiry learning models. This research took place on Fluid Mechanics material on 11th grade of Islamic Senior High School Samarinda. The samples were 108 students out of all students at school as the population. The data obtained were then analyzed using N-gain and inferential statistics. The results showed that the students' HOTS increased significantly with a significance level of 5% after the Inquiry Lab and Guided Inquiry learning model was applied. Based on the calculation of N-gain, there was an increase for the class of 11th Science 2 with very high category (98%), class of 11th Science 1 with high category (83.62%), and a class of 11th Science 3 with low category (34%). Hence, the 11th Science 3 class was statistically significantly different (consistent). The implications of this research for universities include that the curricula for university courses should focus more on mini-research activities, especially those related to open inquiry. Furthermore, there was a significant difference in the effectiveness between the two levels of inquiry and conventional strategies in improving higher-order thinking skills. There are significant differences between the two levels of inquiry, namely Laboratory Inquiry learning and Guided Inquiry itself. The most significant in improving students' HOTs is Laboratory Inquiry.